2019
DOI: 10.4103/jcd.jcd_269_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of remaining dentin thickness following use of three different rotary nickel–titanium retreatment files: A cone-beam computed tomography study

Abstract: Aim: The aim of the study is to measure the amount of remaining dentin thickness (RDT) following retreatment using three different rotary nickel–titanium (NiTi) systems. Methodology: Mesiobuccal roots of 45 extracted maxillary first molars were prepared up to F 2 ProTaper File and obturated. After cone-beam computed tomography (CBCT) imaging, to evaluate the obturation, the samples were randomly assigned to three retreatment groups ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…analysed PTUR file system with D-Race and M-Two systems under cone-beam computerized tomography and concluded that there was no significant difference between the file systems but also said that PTUR removed more dentin, hence substantiating the above results. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…analysed PTUR file system with D-Race and M-Two systems under cone-beam computerized tomography and concluded that there was no significant difference between the file systems but also said that PTUR removed more dentin, hence substantiating the above results. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Retreatment will be initiated and the gutta-percha in the coronal third will be removed using a # 2 Gates Glidden drill 12 . A 40/.06 instrument (Reciproc) 13 will be used for retreatment procedure. After each movement, the le will be removed from the root canal and cleaned.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the complexity of the apical area of the root canal (intracanal isthmuses, constriction, and apical delta), which was observed in the majority of cases, the results of this study revealed that two rotary retreatment systems (R-Endo and EdgefileXR) left filling materials in the canal after retreatment for canals previously obturated by epoxy resin sealer (T-Seal) (30) . The current study found that the EdgefileXR retreatment system for T-Seal sealer was more effective than the R-Endo retreatment system in removing obturating materials.…”
mentioning
confidence: 88%